Proses Monitoring Kampanye Public Relations Dalam Menilai Efektivitas Penyampaian Pesan - Juana Susanti; Rama Yanti; Sri Hertimi (AL-MUNAWWIR: Jurnal Komunikasi, Pendidikan, & Syari'ah, 2026)
Monitoring is an important stage in implementing a PR campaign that serves to observe, measure, and evaluate the effectiveness of message delivery to the audience. This study aims to describe the monitoring process in a PR campaign, analyze the role of monitoring in assessing the effectiveness of message delivery to the audience, explain the use of monitoring results in improving campaign strategies, and identify indicators used to measure message effectiveness. This study uses a qualitative method with a literature study approach. The data used are secondary data obtained from scientific journals, books, research articles and other scientific sources relevant to the research topic. The results show that monitoring is carried out through several stages, namely setting objectives and indicators, data collection, data analysis, and reporting and follow-up. Monitoring plays a crucial role in assessing the effectiveness of message delivery by measuring message reach, level of understanding, involvement, attitude changes, behavior changes, and public response.